2010
DOI: 10.1177/0163443709355607
|View full text |Cite
|
Sign up to set email alerts
|

‘And here’s the news’: analysing the evolution of the marketed newsreader

Abstract: People know me. VC:Well, I'm very happy for you. RB:I'm very important. I have many leather-bound books and my apartment smells of rich mahogany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In 2013, Australian journalist and academic Wendy Bacon led a research project that published some data for news website newmaltida.com.au, concluding that ‘men hold the power at the top of Australian commercial TV’ in news and current affairs. Like Place and Roberts (2006) and Bainbridge and Bestwick (2010), she found that there were almost equal numbers of women and men in television presenting roles. It should be noted that these findings are in contrast to those of Angela Romano’s (2010), whose report for the Global Media Monitoring Project (GMMP) 5 found that just 26% of television (and radio) news stories were presented by a female reporter or newsreader (p. 15).…”
Section: Gender and The Visual Mediummentioning
confidence: 90%
See 3 more Smart Citations
“…In 2013, Australian journalist and academic Wendy Bacon led a research project that published some data for news website newmaltida.com.au, concluding that ‘men hold the power at the top of Australian commercial TV’ in news and current affairs. Like Place and Roberts (2006) and Bainbridge and Bestwick (2010), she found that there were almost equal numbers of women and men in television presenting roles. It should be noted that these findings are in contrast to those of Angela Romano’s (2010), whose report for the Global Media Monitoring Project (GMMP) 5 found that just 26% of television (and radio) news stories were presented by a female reporter or newsreader (p. 15).…”
Section: Gender and The Visual Mediummentioning
confidence: 90%
“…2 Historically, journalism has been a male-dominated occupation, and in television news there has been a prevailing assumption that news is better received by the audience if bulletins are reported and presented by men (Cann and Mohr, 2001: 162). While as early as 1996 Australian television news executives like Terry Plane (cited in Cann and Mohr, 2001) were proclaiming that women were accepted, and even preferred, by female viewers as authority figures, and reporter Peter Ford later suggested that ‘the glass ceiling … for women in Australian television is smashed into a million pieces’ (cited in Bainbridge and Bestwick, 2010: 209), today there are still substantial barriers for women in television. In terms of numerical status across all news platforms in Australia, women remain under-represented at almost every level (Bylery, 2011), most obviously in decision-making roles (North, 2009; 2012a).…”
Section: Gender and The Visual Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…A promo serves to promote a medium while simultaneously constructing an image of it (Bainbridge & Bestwick, 2010). No longer is promotion a secondary tactical device.…”
Section: Media Culture In Times Of Neo-liberalismmentioning
confidence: 99%